Cognition impairment and risk of subclinical cardiovascular disease in older adults: The atherosclerosis risk in communities study - Li, Dongze; Jia, Yu; Yu, Jing; Liu, Yi; Li, Fanghui; Zhang, Wei; Gao, Yongli; Liao, Xiaoyang; Wan, Zhi; Zeng, Zhi; Zeng, Rui (Frontiers in Aging Neuroscience, 2022)
Background: Clinical cardiovascular disease (CVD) and cognition impairment are common and often coexist in aging populations, and CVD is associated with greater cognition impairment risk; however, the association between cognition impairment and CVD risk is inconsistent. It is unknown if pathways that contribute to CVD are caused by impaired cognition. We hypothesized that cognition impairment would be associated with greater subclinical CVD including subclinical myocardial damage (assessed by high-sensitivity cardiac troponin T [hs-cTnT]) and cardiac strain or dysfunction (assessed by N-terminal pro-B-type natriuretic peptide [NT-proBNP]). Methods: This analysis included Atherosclerosis Risk in Communities Study (ARIC) participants who underwent global cognition z-score tests between 1991 and 1993. Cardiac biomarkers were measured from stored plasma samples collected between 1996 and 1999. Logistic regression models were used to determine the association of cognitive function with subclinical CVD risk. Results: There were 558/9216 (6.1%) and 447/9097 (5.0%) participants with incident elevated hs-CTnT (≥14 ng/L) and NT-proBNP (≥300 pg/mL) levels, respectively. Comparing the lowest and highest quartiles of global cognition z-scores, a higher incidence of elevated hs-CTnT (odds ratio [OR]=1.511, 95% confidence interval [CI]: 1.093-2.088, P=0.013) and NT-proBNP (OR=1.929, 95% CI: 1.350-2.755, P<0.001) were observed, respectively. In structural equation modelling, the indirect effect of global cognition z-score on major adverse cardiac events was 42.1% (P < 0.05). Conclusion: Impairments in baseline cognitive function were associated with subclinical myocardial damage or wall strain. Although future studies are warranted to investigate the pathophysiological mechanisms behind these associations, our study suggests common pathways between cognitive and cardiac dysfunction.